Research on the Business English Training Model within MBA Program - Nataliya Yankovskaya; Olga Neklyudova (National Research University Higher School of Economics, 2015)
The paper presents a brief summary of the research on the Business English training model within MBA program students. This study is devoted to the problem of developing a professional foreign language communicative competency of MBA program participants. A particular feature of additional MBA qualification is its international status which presupposes that its graduates (mid-level and top managers) should realize their professional tasks in a foreign language. The analysis of literary works follows in order to find out if activity and competency-based approaches are chosen as instructional bases for developing the model of a business foreign language training that can ensure building a professional foreign language communication competency of the MBA program participants. The result of the study is the model of a business foreign language training that guarantees the development of a professional foreign language communication competency within the process of obtaining additional professional MBA qualification and that includes the following structural components: learning objective, content, a set of forms of organizing the learning process and technological description of each of the five modules. The next part of the paper suggests the result of the research based on testing of the business foreign language training model that guarantees the development of a professional foreign language communication competency when achieving additional professional MAS qualification including a description of the process and the results of assessing the developed dyadic model. The testing consisted of summative and formative assessment and was carried out in the the Russian Presidential Academy of National Economy and Public Administration in several stages (from 1999 to 2007 and then again from 2010 to 2014). When analyzing the results of assessing the dyadic model both the data obtained in control groups (teaching based on the traditional system) and in experimental groups (teaching based on the developed model) were compared. On the basis of the studies the conclusion was made that business English language training, aimed at the development of professional foreign communicative competence of MBA students, organized in accordance with our didactic model, can achieve the goal of real-verbal communication in English in professional environment (business English should become a tool for solving professional problems), and fully meet the needs of students.